Pemeliharaan Hubungan Berpacaran Long Distance Relationship Sampai Ke Jenjang Pernikahan: Studi Pengalaman Menjalani Hubungan Berpacaran Dengan Seorang Pelaut Kapal Kargo - Decyana Ristiani; Hedi Pudjo Santosa; Agus Naryoso (Interaksi Online, 2021)
Long Distance Relationship LDR is described as a form of long-distance romantic relationship, where two individuals are physically separated due to distance (proximity) or geography so that physical contact is limited. In the process, long-distance couples certainly cannot freely meet and express their feelings for each other. In fact, long-distance couples have more complex problems than close-distance courtships, because the greater the distance, the greater the obstacles and challenges that will be faced, especially sailors and students. Therefore, this study describes how a person who works as a Sailor maintains interpersonal communication in a LDR relationship with students and maintains relationships up to the marriage level. In this study, the theory used is the theory of relational maintenance and self-disclosure. The subjects in this study were sailors and students. The writing of this study used qualitative methods with data collection using interviews. The data is then grouped, analyzed using a descriptive phenomenological approach (PFD) and triangulated as a form of data verification. The results of this study indicate that the LDR maintenance process includes intimate relationships between male and female partners by establishing intense communication, then non-intimate relationships which include closeness to the spouse's family and financial distribution. Financial distribution is believed to be a reason to be able to maintain because with the form of financial distribution, the female partner also considers that the commitment undertaken by the male partner is very good and has a high responsibility. In addition, with the financial distribution, the men feel they can bind the female partner to stay committed. These two components will provide a form of influence on a sense of trust, comfort and mutual understanding as well as support from the family which is more important and make the relationship last, so that a perception emerges from them to make a good commitment in maintaining the relationship. The existence of another form of relationship maintenance can be established by having a positive element which means behaving pleasantly and not criticizing. In addition, there is also a need for openness, especially in undergoing a long distance relationship